2001
DOI: 10.1007/s11894-001-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to helicobacter pylori infection in children

Abstract: Helicobacter pylori infection is usually acquired during childhood, and evidence-based guidelines regarding diagnosis and treatment of infected children have been recently published. Diseases associated with H. pylori infection are gastritis, duodenal ulcers, mucosal-associated lymphoid-type (MALT) lymphoma, and gastric adenocarcinoma. The association of specific symptoms with H. pylori infection in children and adults (ie, recurrent abdominal pain and nonulcer dyspepsia) remains controversial. Additionally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 97 publications
1
16
0
Order By: Relevance
“…In addition, the prevalence of AG and IM in males were significantly higher than those in females. It is generally understood that the prevalence of H. pylori infection and gastric disorders in males is more common than that in females 16,17. Furthermore, seropositivity of H. pylori was found to be the risk factor of AG and IM in the present study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, the prevalence of AG and IM in males were significantly higher than those in females. It is generally understood that the prevalence of H. pylori infection and gastric disorders in males is more common than that in females 16,17. Furthermore, seropositivity of H. pylori was found to be the risk factor of AG and IM in the present study.…”
Section: Discussionsupporting
confidence: 58%
“…H. pylori infection usually occurs in the childhood, but AG and IM progress in the elderly population due to long infectious periods with H. pylori 17. In addition, the prevalence of AG and IM in males were significantly higher than those in females.…”
Section: Discussionmentioning
confidence: 94%
“…[4041] Hence, the possible routes are feco–oral, oral–oral and gastro–oral. [42] Thomas et al were able to isolate H. pylori DNA and culture H. pylori from human feces, suggesting a feco–oral transmission. [43] Oral–oral transmission has also been recognized because H. pylori was isolated from dental plaques and saliva.…”
Section: Transmission Of H Pylori Infectionmentioning
confidence: 99%
“…18 Evidence also supports child-to-child transmission among those in crowded school or living conditions as well as in chronic care facilities for multiple handicapped children. 1 In contrast, transmission among adults is rareadults have a H pylori seroconversion rate of approximately 0.3% per person-year. Studies of families have found that one spouse may be positive, whereas the other remains negative, and that an uninfected parent remains negative even if children in the household are infected.…”
Section: Infection With H Pylori: Risk Factors and Acquisitionmentioning
confidence: 99%
“…1 Infection with H pylori has also been linked pathologically to the development of gastric cancer. Worldwide, infection with H pylori is highly prevalent-approximately 50% of the world population is infected, with prevalence rates in countries ranging from 20% to more than 80%.…”
mentioning
confidence: 99%